Essays on Strategic Management: Exploring the Effects of Cooperative and Competitive Firm Strategies on Firm Performance - Brede, Marius; Justus Liebig University Giessen (My University, 2024)
This cumulative dissertation advances strategic management research by exploring how interorganizational networks and organizational culture shape firm behavior and performance. Building on resource dependence theory, agency theory, organizational learning theory, and cultural frameworks, it examines both cooperative and competitive firm strategies in three interrelated studies. (1) Board Interlocks and Firm Performance: A Meta-Analysis This study synthesizes findings from 119 primary studies and over one million board interlocks to investigate the dual role of interlocking directorates. Using meta-analytic structural equation modeling, it identifies two opposing mechanisms—resource provision and agency costs—and demonstrates that the effect of board interlocks on firm performance is contingent on CEO power and the institutional environment. (2) Resource Appropriation in Strategic Alliances: The Influence of Board Interlocks on Differential Benefits Employing event study methodology and network analysis on over 2,000 strategic alliances, this study shows that both direct and indirect board interlocks can lead to unequal value appropriation between partners. While such ties facilitate knowledge transfer, they also enable opportunistic behavior when power asymmetries exist. The study underscores the context-dependent nature of interlocks, particularly in alliances characterized by weak governance or low receptivity. (3) Mind the Gap: The Effect of Cultural Distance on Mergers and Acquisitions – Evidence from Glassdoor Reviews Drawing on a novel dataset of more than 300,000 employee reviews and applying natural language processing techniques, this study introduces an innovative measure of organizational cultural distance. It finds that cultural misalignment between acquirer and target negatively affects both market reactions and long-term performance, and inflates acquisition premiums due to flawed synergy expectations. Moreover, cultural distance impedes post-merger innovation. Taken together, the dissertation demonstrates that firms’ strategic outcomes are co-determined by the social structures they are embedded in and the cultural compatibility they maintain. It contributes to the emerging network and culture paradigms in strategy research by integrating large-scale data with nuanced theoretical insights and by showing that leveraging intangible, relational assets is key to sustainable competitive advantage.
Keywords: strategic management; board interlocks; meta-analysis; network analysis; mergers & acquisitions; organizational culture; ddc:330